2016
DOI: 10.1161/strokeaha.115.012133
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Derived Pentraxin 3 Supports Blood–Brain Barrier Integrity Under Acute Phase of Stroke

Abstract: Background and Purpose Pentraxin 3 (PTX3) is released upon inflammatory responses in many organs. However, roles of PTX3 in brain are still mostly unknown. Here we asked whether and how PTX3 contributes to blood-brain barrier (BBB) dysfunction during the acute phase of ischemic stroke. Methods In vivo, spontaneously hypertensive rats were subjected to focal cerebral ischemia by transient middle cerebral artery occlusion. At day 3, brains were analyzed to evaluate the cellular origin of PTX3 expression. Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 36 publications
5
97
0
1
Order By: Relevance
“…59,60 In addition to these properties, astrocytes acquire the capacity for producing pro-inflammatory factors and antigen-presentation upon brain ischemia. 61,62 This suggests the possibility that activation of astrocyte may promotes ischemic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 In addition to these properties, astrocytes acquire the capacity for producing pro-inflammatory factors and antigen-presentation upon brain ischemia. 61,62 This suggests the possibility that activation of astrocyte may promotes ischemic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that the levels of acute phase protein increased in a variety of neurodegenerative diseases [36, 37]. For instance, Lee et al have observed high plasma PTX3 levels in idiopathic PD patients and found significant correlation between the PTX3 levels and daily life activities and motor functions [38].…”
Section: Discussionmentioning
confidence: 99%
“…These exosomes, when isolated from BM-MSCs, appear to be 50–100 nm in size, display CD81, CD9, and Alix exosome-associated proteins, and have a lipid membrane identity consisting of cholesterol, sphingomyelin, and phosphatidylcholine (Lai et al, 2010). BM-MSCs express multiple trophic factors which may function to protect and support neurons in ischemic conditions, including BDNF, NGF, thrombospondin1, pantraxin3, VEGF, bFGF, and placental growth factor, as well as therapeutic microRNAs, such as microRNA 133b (Eckert et al, 2013; Park et al, 2015; Shichinohe et al, 2016; Xin et al, 2016). Importantly, BM-MSCs play a potent role in the sequestration of neuroinflammation.…”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%
“…From the data available, we can postulate that if these cells, which can differentiate into endothelial-like cells, do regulate the immune environment post-stroke, such effects might arise via restoration of the BBB and its subsequent decreased permeability to circulating inflammatory cell types or general paracrine effects on pro-inflammatory immune sources (Borlongan et al, 2012; Garbuzova-Davis et al, 2014). In addition, because breast milk-derived stem cells can differentiate into astrocytes, which can produce pentraxin 3, a compound that promotes BBB integrity after ischemic stroke, breast milk-derived stem cells may have the capacity to encourage suppression of peripheral immune invasion (Shindo et al, 2016). To this end, an active component in breast milk, milk fat globule-EGF factor 8 protein, has anti-inflammatory effects in models of inflammatory bone loss, suggesting, perhaps, an a role for breast milk-derived components in abrogating neuroinflammation following stroke (Abe et al, 2014).…”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%